Lone parent transitions, employment transitions and poverty outcomes - Helen Russell; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2024)
Lone parent families are consistently identified among those most at risk of poverty and deprivation in Irish society, which causes the members of these families short- and long-term harm. In this study we draw on the Growing Up in Ireland study (GUI) 08 Cohort, using four waves of data from 2008 to 2017, when the study child was aged 9 months to 9 years. We examine the relationship between family trajectories, economic vulnerability and employment among lone parent households. The aim is to understand the contexts and social factors that lead to the association between lone parenthood and economic vulnerability.
Keywords: 330